Implementasi Load Balancing dan Failover pada Proses Migrasi Container Docker - Shofura Naufal Rifiera; Heru Nurwarsito (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The rapidly increasing use of the internet today will of course have a major impact on the performance of a web server. The web server cannot respond quickly so that it can hamper the communication process. The availability of a web server that is not supported by a method can hamper the performance of a server, due to the accumulation of requests on the server which can cause network failure. For this reason, a dynamic web server implementation planning process was formed by implementing a docker system with the failover method to be able to dynamically take over the connection when one of the servers is down is proposed to overcome this problem. Based on the research on the implementation of dynamic web servers by implementing Docker, it can be concluded that the implementation of dynamic web servers with Docker as containerization management on virtual networks. With the facilitation of the web server image, it can be used to run an open source service as a web server by implementing the PHP language to be displayed on HTML pages that are directly connected to the data base as storage media. With loadbalancing and failover mechanisms in the docker environment, it is very helpful in distributing web server services from node manager to node worker as a backup server in the event of a system failure on one of the servers. Then the dynamic web server in failover testing has the lowest average response time at node worker 2 with a value of 18.90ms, the time obtained is certainly influenced by the delay time interval that has been determined during load testing of the web server service.